Akurasi Hitung Jumlah Eritrosit Metode Manual dan Metode Otomatis - Oktiyani, Neni; fahriyan, fahriyan; Muhlisin, Akhmad (Medical Laboratory Technology Journal, 2017)
In a laboratory, an erythrocyte is done by using hemocytometer and microscope. The task is to measure and assess the size and shape of the erythrocyte. But this procedure is time consuming, complex and tedious. As a solution to this problem, to provide an automated, cost-effective and efficient alternative to detection and counting of erythrocyte, hematology analyzers are used. However, false results related either to erythrocyte or other parameters from complete blood count may be observed in several instances. The objective study was to compare the accuracy of erythrocyte count results of automatic hematological analysis by the manual method. The study is an analytic survey with a cross-sectional design. Erythrocyte counting is done by using three types of control blood, namely high, normal and low, with 9 repetitions. In high control blood, the mean erythrocytes count by the manual method was 7.08 million/μl with a bias value of 1.4%, while that by the automated method was 7.03 million/μl with a bias value of 0.7%. The mean erythrocyte count in normal control blood by the manual method was 4.50 million/μl with a bias value of 0.9%, while that by the automated method was 4.4 million/μl with a bias value of 2.4%. And in low control blood, the mean erythrocyte count by the manual method was 1.72 million/μl with 4.4% bias value, while that the automated method was 1.67 million/μl with 1.2% bias value. Statistical analysis showed no significant difference in accuracy between the erythrocyte count of manual methods with automated methods.